2022
DOI: 10.1155/2022/4921211
|View full text |Cite|
|
Sign up to set email alerts
|

Intelligent Research Based on Deep Learning Recognition Method in Vehicle-Road Cooperative Information Interaction System

Abstract: The vehicle-road collaborative information interaction system is an emerging technology system that realizes the sharing of information between vehicles, vehicles and roads between traffic road information, and driving vehicle information. It is of positive significance for improving the urban transportation construction system and promoting urban economic development. This paper conducts intelligent research on the deep learning recognition method based on the vehicle-road collaborative information interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Among these, accuracy and recall are two important indicators used to evaluate the performance of the YOLOv5 object-detection system. The accuracy rate refers to how many of the objects detected by the object detection system are correct, and the recall rate refers to the probability that the real object is detected [31]. In general, the higher the correct rate, the higher the recall rate, and the better the performance of the system.…”
Section: Model Evaluation Indicatorsmentioning
confidence: 99%
“…Among these, accuracy and recall are two important indicators used to evaluate the performance of the YOLOv5 object-detection system. The accuracy rate refers to how many of the objects detected by the object detection system are correct, and the recall rate refers to the probability that the real object is detected [31]. In general, the higher the correct rate, the higher the recall rate, and the better the performance of the system.…”
Section: Model Evaluation Indicatorsmentioning
confidence: 99%
“…Balakrishnan presented the Faster RCNN ResNet101 algorithm, which was used to detect the number of false ceilings [47]. A deep learning recognition and counting method for the vehicle-road collaborative information was conducted by Hongbin Jiao [48]. Zishuo Huang and Qinyou Hu proposed an improved single shot multibox detector and DeepSORT algorithms and performed numerical experiments, indicating that the ship counting system is more accurate [49].…”
Section: Object Countmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%